The use of microalgae as a high-value organic slow-release fertilizer results in tomatoes with increased carotenoid and sugar levels - Coppens, Joeri; Grunert, Oliver; Van Den Hende, Sofie; Vanhoutte, Ilse; Boon, Nico; Haesaert, Geert; De Gelder, Leen (Journal of applied phycology, 2016)
The heightened awareness concerning environmental preservation, resource scarcity, food safety, and nutrition has engendered the need for a more sustainable and resource-efficient agricultural production system. In this context, microalgae offer the potential to recover nutrients from waste streams and subsequently use the microalgal biomass as a sustainable slow-release fertilizer. The aim of this study was to assess microalgal bacterial flocs treating aquaculture wastewater and marine microalgae as organic slow-release fertilizers for tomato cultivation. Comparable plant growth was observed using microalgal and commercial organic fertilizer treatments. Furthermore, the microalgal fertilizers improved the fruit quality through an increase in sugar and carotenoid content, although a lower tomato yield was obtained. An economic evaluation indicates the economic feasibility of the microalgae-based fertilizers. Further research is required to optimize the microalgae-based fertilizer composition.